Die unvollendete Bankenunion - Lederer, Gerald (2023)
This book examines the various legal and soft law instruments used at EU level in an attempt to ensure uniform regulatory conditions in the area of banking union. In doing so, the author covers a very broad spectrum in which the most diverse forms of action are examined from a genuinely administrative law perspective on the basis of Austrian and EU constitutional law. The result is a comprehensive and clear picture of the available legal acts in one of the most dynamic areas of public law.